Case Report: Identification of Potential Prognosis-Related TP53 Mutation and BCL6-LPP Fusion in Primary Pituitary Lymphoma by Next Generation Sequencing: Two Cases - Zhang, Yi; Ma, Liyuan; Liu, Jie; Zhu, Huijuan; Lu, Lin; Deng, Kan; Ma, Wenbin; Pan, Hui; Wang, Renzhi; Yao, Yong (Frontiers in Endocrinology, 2021)
Background: Primary pituitary lymphoma (PPL) is an extremely rare disease with poor prognosis. Although PPL has been shown to be different from classical primary central nervous system lymphoma because of the embryological origin of structures, individual and precise treatment of PPL remains unknown. Methods: A 61-year-old man and a 65-year-old woman both diagnosed with primary pituitary diffuse large B cell lymphoma underwent genetic analysis of cerebrospinal fluid and tumor tissue by next generation sequencing. Results: In the first case, partial remission was achieved following R²-MTX chemotherapy. In the other case with TP53 mutation and BCL6-LPP fusion, disease progressed although different chemotherapy regimens were given. Conclusion: The gene mutation of TP53 and BCL6 may be identified as a marker responsible for prognostic difference in patients with PPL. Genetic analysis may provide a novel approach for precise management and prognosis prediction.